Advance care planning in dementia: recommendations for healthcare professionals. (February 2019) - Harrison Dening, Karen; Sampson, Elizabeth L; De Vries, Kay
The process of advance care planning in dementia is far from straightforward; as dementia progresses, the ability to consider future thoughts and actions becomes compromised, thus affecting decision-making abilities. Family carers find themselves increasingly in a position where they need to inform, or directly make, decisions on behalf of the person with dementia. This article discusses the context and importance of a palliative care approach and recommends rationales and strategies for healthcare professionals to support families affected by dementia to better plan for their future care.